Metaphor and Meaning in Arabic Political Discourse/ الاستعارة والمعنى في الخطاب السياسي العربي - Karim Yusufy; Johan Mille (IJAS: International Journal of Arabic Studies, 2025)
This study explores the role of metaphor in shaping meaning within Arabic political discourse. Metaphor is not merely a rhetorical ornament but a cognitive and strategic tool that constructs social and political realities. Through a qualitative discourse analysis of selected Arabic political speeches, media texts, and official statements, the research identifies dominant metaphorical patterns such as war, medical, religious, and economic metaphors. These patterns reveal how political actors simplify complex issues, mobilize public emotions, and legitimize their agendas. The findings highlight that war metaphors intensify polarization and mobilization, while medical and religious metaphors enhance legitimacy and moral authority. Economic metaphors, on the other hand, reflect the influence of globalization and neoliberal discourse. The study concludes that metaphor is central to the production of political meaning in Arab societies, bridging language, culture, and ideology. This research contributes to a deeper understanding of how language functions as a vehicle of power in Arabic political contexts.